The Role of Social Support in Iron Folic Acid Supplement Adherence Among Adolescent Girls in a Public Junior High School in Jakarta - Christin Jayanti; Olviany Ayu Anggraeni (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Iron deficiency anemia remains a pressing public health issue among adolescent girls, particularly in Southeast Asia. Despite the implementation of school-based weekly iron-folic acid (Fe) supplementation programs in Indonesia, adherence rates remain suboptimal. This study aimed to examine the association between family, teacher, and peer support and adherence to Fe tablet consumption among adolescent girls in DKI Jakarta Province. A quantitative, cross-sectional study was conducted in December 2024 at SMP Negeri 79 Jakarta. A total of 57 female students aged 12-15 years were selected through purposive sampling, based on their participation in the school-based Fe tablet supplementation program. Data were collected using structured, pre-validated questionnaires assessing levels of social support and adherence to Fe tablet intake, with adherence defined as consuming ≥75% of the recommended dosage over the previous four weeks. Statistical analysis was performed using the Spearman Rank correlation test via SPSS version 25.0, with significance set at p < 0.05 and a 95% confidence interval (CI). The findings revealed that most participants received low family (56.1%) and peer support (59.6%), while teacher support was reported as high in 42.1% of respondents. Only 24.6% of participants were categorized as adherent. Significant positive correlations were observed between adherence and family support (r = 0.724; 95% CI: 0.57-0.84), teacher support (r = 0.555; 95% CI: 0.34-0.72), and peer support (r = 0.677; 95% CI: 0.48-0.80), with all associations statistically significant at p < 0.001. Family, teacher, and peer support are critical determinants of adherence to iron-folic acid supplementation among adolescent girls. Strengthening multi-level social support mechanisms within school health programs could significantly enhance compliance and contribute to the prevention of anemia in this vulnerable population Keywords: Iron Folic Acid Supplementation, Adolescent Health, Social Support, Compliance